Relationship Between Environmental Changes and Waste Management Policies on the Formation of the Quality of Life in Poland. A Regional Approach - DZIEKAŃSKI PAWEŁ; POPŁAWSKI ŁUKASZ (Zagadnienia Ekonomiki Rolnej, 2025)
The aim of the study is to assess the impact of environmental change and waste management policies on the quality of life of county population in Poland, taking into account their spatial differentiation.